PEMBINAAN DAN MAINTENANCE PERALATAN KESEHATAN DI PUSKESMAS PEMBANTU CANGGU - Mahardiananta, I Made Agus; Suhartono, Suhartono; Istri Dharmayanti, Cokorda; Gunawan, I Kadek Agus Riki; Gunawan, I Putu Adi Surya (Jurnal Abdi Insani, 2024)
Community service is one of the important pillars in the Tri Dharma of Higher Education in Indonesia, which includes education, research and community service. Within the scope of electromedical engineering, community service has a very strategic role in supporting improving the quality of public health. The aim of community service activities at the Canggu sub-district health center is to provide guidance related to health equipment maintenance, which includes equipment inventory activities, equipment repair and socialization on the use of health equipment. By carrying out this service activity, it is hoped that a better and more sustainable health system will be created at the Canggu sub-health center. The method used in this activity is socialization and checking equipment directly in the field. As a result of service activities at the Canggu sub-health center, almost all equipment could be repaired, but there was one device, namely the vaccine refrigerator, which could not be repaired and recommendations were given for repairing spare parts. As well as increasing insight into the operation of medical equipment used so that it is always active, accurate, and of course can help medical activities.